PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH: KOMITMEN ORGANISASI, BUDAYA ORGANISASI, DAN GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI - Arifin, Solikhun; Rohman, Abdul (Diponegoro Journal of Accounting, 2012)
This study aims to analyze whether participation budget significantly affect employee performance, but it also aims to determine whether situational factors such as organizational commitment, organizational culture and leadership style can affect the relationship between budgetary participation on employee performance. There are differences between this study with previous research conducted by Sardjito and Muthaher (2007), Nurcahyani (2010), Wulandari (2011), Kurniawan (2011), and Mattola (2011). Previous research has not paid attention leadership style variables as moderating variables. In addition, in previous studies of organizational culture variables significantly affect the performance of the apparatus. The sampling method used was purposive sampling and obtained a sample of 117 respondents from 32 SKPD Semarang. The research was conducted in 2012 and using primary data obtained by distributing questionnaires. Questionnaires budgetary participation and organizational commitment modified by Nurcahyani (2010). Employee performance questionnaire modified by Wulandari (2011). Organizational culture questionnaire was modified by Kurniawan (2011). Questionnaires leadership style modified by Budget (2011). The four study discusses the performance of public sector officials. While the original research which is used as the main reference is Sardjito research and Muthaher (2007). The process of data analysis is the test of non-response bias, continued the classical assumption test, followed by hypothesis testing. Testing in this study using SPSS software version 17 for windows. Results showed that participation angggaran preparation significantly affect the performance of the apparatus, with employees participating in the budgeting process, they also feel responsible for the success of the program that had previously been discussed with them. In addition, in this study there are also situational factors that can significantly affect the performance of the apparatus is the organization's commitment and leadership style. High levels of organizational commitment that will make people more interested in the organization rather than self-interest, so that each individual will always improve performance because they will not rest until the organization can achieve the desired objectives. Similarly, the leadership style factors, this study proves that the style of leadership that is based on mutual trust, kinship, appreciate the idea of ​​subordinates and the open communication (consideration) can significantly improve the performance of government officials.